From university to community: challenges in service-learning implementation - Maulan, Sumarni; Omar, Nur Hidayatulshima; Maulan, Sumarni (Universiti Teknologi MARA, Kedah, 2024)
In the recent years, a number of higher educational institutions has adopted service-learning as part of their curriculum, and it has received a significant attention from academicians and researchers across discipline. Despite the variety of benefits associated with service-learning such as enhanced social responsibility and civic leadership among students, increased student learning and practical experience, there are also challenges faced by them in incorporating and applying the theories learnt in the classroom to the real-world scenario. To investigate the problems faced by the students, a six-stage thematic analysis (TA) (Braun & Clark, 2006) was used to code the data derived from 22 respondents of an open-ended questionnaire. Seven themes were found in relation to the challenges: communication, self-management, leadership, cognitive, teamwork, ethics and professionalism and financial. The results provide some insights into pedagogical practices that can be employed by educators to better prepare the students for their future engagement with the community.